A Laboratory Setup for an Introduction to Fractional Order Systems. Issue 9 (2019) - Radici, Alberto; Chen, YangQuan; Padula, Fabrizio; Visioli, Antonio
Abstract: In this paper we propose the use of a simple laboratory setup, which consists of a Peltier cell system, to introduce students to fractional-order systems. The setup can be built by using simple and low-cost components and can be used, by simply evaluating a step response, to show the need of using fractional-order models to accurately describe some real-world physical systems. A possible extension of the system is also described. In addition to fractional systems modeling, also the implementation of fractional control systems can be considered for a more advanced treatment of the topic.